The Causality between Oil price, Financial Market Uncertainty and Economic Policy Uncertainty in the United States - Prabhakar, Saimanish; Kalaitzi, Athanasia Stylianou (International Journal of Energy Economics and Policy, 2026)
This study investigates the causal relationships between uncertainty measures and oil price dynamics, using monthly data over the period from February 1990 to September 2024. The autoregressive distributed lag model (ARDL) bound test is applied to examine the existence of a long-run relationship between the variables, while the Granger causality test in a Vector Autoregressive (VAR) framework is conducted to examine the direction of the short-run causality. To investigate the long-run causal relationships between uncertainty and oil prices, the Toda and Yamamoto test in an Augmented VAR (AVAR) is performed. The empirical results reveal no long-run cointegration among the variables. In the short run, there is a unidirectional causality from oil prices to economic policy uncertainty, while financial market uncertainty directly causes oil price movements. Additionally, both uncertainty measures indirectly cause oil prices through oil demand. The long-run causality results indicate a bidirectional causality between oil prices and economic policy uncertainty, while a unidirectional causality runs from financial market to oil prices. In addition, oil supply and financial market uncertainty indirectly cause oil prices through economic policy uncertainty. Unlike the short-run findings, the long-run results suggest that uncertainty does not cause oil prices through the demand channel.